Inequities to the access to and use of telemedicine among cancer patients in Europe: a scoping review - Leclercq, Victoria; Vandervliet, Léopold; Schmitt, Tugce; Van den Bulcke, Marc; Delnord, Marie (Frontiers in Public Health, 2025)
IntroductionOver the last few years, telemedicine (TM) services have increasingly been used in European health and care systems. TM services include remote assistance with teleconsultation and telemonitoring. Several sources highlight that TM services may widen existing inequities in health. Therefore, this study aimed to identify barriers and facilitators contributing to inequities to TM among cancer patients in Europe.MethodsMedline (via Ovid) and Scopus databases were searched for all publications providing evidence on factors influencing the access to and use of TMs among cancer patients aged 18 and over in Europe published between January 2018 and March 2023. The PROGRESS-plus framework was used to map health equity factors in TM services among cancer patients.ResultsA total of 2072 peer reviewed publications were identified and after screening, 26 articles were retained in our scoping review. Only studies focused on TM used by cancer patients through mobile or web-based applications were included. In terms of access to TM, people with lower socioeconomic status, including difficulties with having an internet connection and not having their own mobile device, and language barrier seem to have less access to TM services. For the use of TM services, a lower level of education, few digital skills and (e-)health literacy, lack of social support, age and presence of comorbidities are important determinants.DiscussionBetter integration of patient needs in TM is necessary to enhance equity and allow a better implementation of TMs in European health and care systems aligned with different initiatives such European Beating Cancer Plan.